2023
DOI: 10.2147/idr.s433186
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Azvudine and Nirmatrelvir/Ritonavir and Combined Use in Patients with COVID-19

Cheng-Yi Hu,
Wen-Shuai Cui,
Yi Lei
et al.

Abstract: To compare the effectiveness of azvudine and nirmatrelvir/ritonavir for the treatment of coronavirus disease . Patients and Methods: We conducted a retrospective analysis of data from 576 patients with COVID-19, comprising 195 patients without antiviral therapy, 226 patients treated with azvudine, 114 patients treated with nirmatrelvir/ritonavir, and 41 patients were treated with azvudine and nirmatrelvir/ritonavir concurrently. We compared their symptoms, mortality rates, and the length and cost of hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The initial literature search yielded 84 articles, of which 25 considered eligible for full-text review following title and abstract screening. After the full-text review, 12 studies were excluded due to control type and insufficient data, resulting in the inclusion of 13 articles [20][21][22][23][24][25][26][27][28][29][30][31][32] involving 4949 patients for the metaanalysis. All included studies were retrospective cohort designs, and the mean patient age across the studies ranged from 14 to 66.2.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial literature search yielded 84 articles, of which 25 considered eligible for full-text review following title and abstract screening. After the full-text review, 12 studies were excluded due to control type and insufficient data, resulting in the inclusion of 13 articles [20][21][22][23][24][25][26][27][28][29][30][31][32] involving 4949 patients for the metaanalysis. All included studies were retrospective cohort designs, and the mean patient age across the studies ranged from 14 to 66.2.…”
Section: Search Resultsmentioning
confidence: 99%
“…A total of 10 studies 20,21,[24][25][26][27][28][29][30][31] involving 4672 patients reported mortality rates among COVID-19 patients treated with azvudine or Paxlovid. The pooled estimate indicated no significant difference in mortality rate between the azvudine and Paxlovid groups (OR = 0.84, 95% CI: 0.59-1.21; p = 0.37, I 2 = 55%, GRADE certainty: moderate) (Figure 2).…”
Section: Mortality Ratementioning
confidence: 99%
See 1 more Smart Citation